CITRA PERJUANGAN PEREMPUAN DALAM NOVEL SING ME TO SLEEP (ANALISIS FEMINISME) - Tiara Noviarini (Center of Gender Studies and Child of State Islamic Institute of Metro, 2021)
This study aims to determine the kinds of women's struggles to get their love in the novel Sing Me to Sleep. This research uses descriptive qualitative methods and a theory focused on the character of Virginia Woolf. The author uses note-taking as a research instrument. The author found that there are three kinds of women's struggles. Namely, first the struggle to accept the reality of life, the second the struggle to achieve dreams, and finally the struggle in the form of love, and the struggle to get love